Between Tradition and Counter-Tradition:: The Poems of A.J.M. Smith and F.R. Scott in The Canadian Mercury (1928-29) - Richards, Alan (Studies in Canadian Literature / Études en littérature canadienne, 2005)
The contents of The Canadian Mercury (1928-29), especially the poems of A.J.M. Smith and F.R. Scott, embody the kind of struggle with which an emerging strain of vitalizing modernism attempts to counter a prevailing strain of late Canadian Romanticism. Both Smith and Scott decry excessive description and precious diction, but their attempts to depart from the Romantic aesthetic are only partly successful. Because they represent an early attempt to establish a new poetry but still manifest some structural and aesthetic elements of Romanticism, the poems of Smith and Scott exemplify The Canadian Mercury's transitional poetics: between the dominant tradition in early twentieth-century Canadian poetry and the modernism that would replace it.